GROWTH MONITORING TRAINING AND CHILD DEVELOPMENT FOR PRESCHOOL TEACHERS IN THE FRAMEWORK OF STUNTING OVERCOMING - Uun Kunaepah; Priyo Sulistiyono; Eva Dwi Alviani; Nining Rukniah; Siti Fatimah; Muhammad Khairul Akmal; Muhammad Asrulhaimi; Jihan Mujahidah Aziz (Ann Publisher, 2024)
The prevalence of stunting in Indonesia fell from 24.4% in 2021 to 21.6% in 2022. The stunting figure is still quite high compared to the government's target of 14% in 2024. Stunting is one of the government's priority programs, considering the impact of stunting on the quality of human resources is very large. PAUD/Kindergarten teachers academically have the potential intellectual abilities to provide input on the importance of children's growth, in addition to children's abilities or intelligence. The service activities aim to increase the capacity of PAUD/TK teachers in monitoring children's growth and development according to standards The activity method is training in monitoring the growth and development of early childhood. Activities in collaboration with partners, namely HIMPAUDI, Sunyaragi District and Sunyaragi Community Health Center, Cirebon City. Collaboration by sharing resources between study programs and partners. The measuring parameters use the pre-post knowledge and ability values ​​of participants in carrying out practical assignments to monitor growth and development in child cases. This activity is expected to increase the capacity of PAUD teachers in monitoring the growth and development of their students according to standards. This activity was carried out at the HIMPAUDI Secretariat, Cirebon City, attended by 25 PAUD teachers representing 5 (five) sub-districts in Cirebon City. As a result of this training activity, PAUD teachers understand better about anthropometric measurements, growth and development of early childhood based on the results of the pre and post test scores carried out. The teachers were very enthusiastic about participating in the training until it was finished. The outputs that have been created are training modules, activity videos, publication drafts in newspaper media and publication journals in the Community Service Journal in the process of being prepared.